Le développement dans l’optique du marketing : le cas des produits agricoles dans les P.V.D. - Hénault, Georges (Études internationales, 1980)
The author seeks to determine in what way marketing may be considered as a development catalyst by examining the case of agricultural products in developing countries. He first observes that the marketing System both reflects the level of development and constitutes a subsystem of the socio-economic System. Marketing is thus in a symbiotic relationship with the development process.Market complexity conditions the nature of public and private sector initiatives. In fact, the structure of domestic agricultural markets is disjointed and the imperatives of world markets impose an almost dialectical choice between exports and import substitution. After having analyzed contextual and empirical data, the author considers such marketing actors as government marketing boards and producer cooperatives by attempting an assessment of their developmental impact. Marketing, he concludes, may be seen as a necessary but not sufficient condition for the development process.